Handbook of biophilic city planning and design - Beatley, Timothy, 1957- (Washington, DC : Island Press, 2016)
"This publication offers practical advice and inspiration for ensuring that nature in the city is more than infrastructure--that it also promotes well-being and creates an emotional connection to the earth among urban residents. Divided into six parts, the Handbook begins by introducing key ideas, literature, and theory about biophilic urbanism. Chapters highlight urban biophilic innovations in more than a dozen global cities. The final part concludes with lessons on how to advance an agenda for urban biophilia and an extensive list of resources."--Publisher.
Part 1: The background and theory of biophilic cities. -- Chapter 1. The power of urban nature : the essential benefits of biophilic urbanism -- Chapter 2. Understanding the nature of biophilic cities -- Chapter 3. The urban nature diet : the many ways that nature enhances urban life -- Chapter 4. Biophilic cities and urban resilience -- Part 2: Creating biophilic cities : emerging global practice. -- Chapter 5. Singapore City, Singapore : city in a garden -- Chapter 6. Milwaukee, Wisconsin : from cream city to green city -- Chapter 7. Wellington, New Zealand : from town belt to blue belt -- Chapter 8. Birmingham, United Kingdom : health, nature, and urban economy -- Chapter 9. Portland, Oregon : green streets in a river city -- Chapter 10. San Francisco, California : biophilic city by the bay -- Chapter 11. Oslo, Norway : a city of fjords and forests -- Chapter 12. Vitoria-Gasteiz, Spain : nature in the compact city -- Part 3: A global survey of innovative practice and projects. -- I. Biophilic plans and codes -- II. Citizen science and community engagement -- III. Biophilic architecture and design -- IV. Restoring and reintroducing nature into the city -- V. Other biophilic urban strategies -- Part 4: Successes and future directions. -- Chapter 13. Lessons from the world's emerging biophilic cities -- Chapter 14. Overcoming the obstacles and challenges that remain -- Chapter 15. Conclusions : reimagining cities of the future.
Includes bibliographical references (pages 265-278) and index.
Keywords: City planning -- Environmental aspects; Sustainable development; Human ecology; ARCHITECTURE -- Sustainability & Green Design; ARCHITECTURE -- Urban & Land Use Planning; NATURE -- Environmental Conservation & Protection; Architecture and Planning; City planning -- Environmental aspects; Human ecology; Sustainable development; Architecture and Planning